Evaluation Of Existing Software For Simulating Of Crowd At Masjid Al-Haram, - Sarmady, S.; Haron, F.; Mohd Salahudin, M.M.; Talib, A.Z.H. (2007)
Crowd simulation has played an important role in solving situations such as building evacuation, crowd congestion, and pedestrian analysis. In order to improve the crowd congestion problem within and the surrounding area of the Masjid Al-Haram, we need a tool which could reproduce specific scenarios and study the possible controls that could ease the problem. This paper explains the criteria to be considered in evaluating the crowd simulation software for the Masjid Al-Haram under both, normal and emergency situations. Our study has led us to the most suitable software package that meets our requirements. We have also identified the main features that we should (later) incorporate in our own design of the simulation system of the Masjid Al-Haram.